Fingerprint as a Means of Internal Identification The Crime of Murder (Study at Pematang Siantar Police Station) - Putri Sari Tampubolon (IHSA Institute, 2022)
The crime of murder today is one of the most complicated and very serious problems faced by individuals, society, law enforcement, and the government. The impact of this act of killing is felt very strongly by the community, namely the disruption of security and order in society. Therefore, this crime of murder needs to be handled or tackled seriously. Which in the handling or mitigation is closely related to the role of the Indonesian National Police as their role as investigators and investigators, to uncover the occurrence of a criminal act of murder, the initial procedure carried out by the police is an investigation to seek and find an incident that is suspected of being a murder crime, to then determine whether or not further action can be taken, namely an investigation. It is in this part of the investigation that the Police can take the first step, namely managing the crime scene (TKP) by identifying any evidence found such as objects that are strongly suspected of being related to the incident, including the victim, objects around the victim or in the vicinity of the victim. around the crime scene. And for the purposes of investigation, the Police are authorized or entitled to take several actions that have been regulated or determined by the Law on the Indonesian National Police No. 2 of 2002 in Article 15 paragraph (1), including taking fingerprints and other identities and taking pictures of someone. This is the reason behind the author's interest in writing a thesis with problems including: How is the process of formulating fingerprints (dactyloscopy) in identifying a crime of murder; What is the role of fingerprints as a means of identification in a murder crime and what are the obstacles faced in the process of identifying a murder crime by using fingerprints as a means of identification.